Recommendations of the Committee for Waterfront Structures Harbours and Waterways EAU 1996 /issued by the Committee for Waterfront Structures of the Society for Harbour Engineering and the German Society for Soil Mechanics and Foundation Engineering. - Arbeitsausschuss "Ufereinfassungen" (Germany)
"English translation of the 9th German edition."